An eye for an eye [large type] - Archer, Jeffrey, 1940- (Archer, Jeffrey, 1940- William Warwick novels, 2024)
"In one of the most luxurious cities on earth, a billion-dollar deal is about to go badly wrong. A lavish night out is about to end in murder. And the British government is about to be plunged into crisis. In the heart of the British establishment, Lord Hartley, the latest in a line of peers going back over two hundred years, lies dying. But his will triggers an inheritance with explosive consequences. Two deaths. Continents apart. No obvious connection. So why are they at the center of a master criminal's plot for revenge? And can Scotland Yard's elite squad uncover the truth before it's too late?"--